Polyethyleneimine modified graphene oxide composite material as well as preparation method and application thereof
By using polyethyleneimine modified graphene oxide composite materials as shale inhibitors, the problems of existing inhibitors inhibiting hydration, filtration loss and insufficient temperature resistance during drilling are solved, and more efficient shale control and drilling stability are achieved.
Patent Information
- Application Number
- CN202311132887.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-04
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-09-04
AI Technical Summary
Existing shale inhibitors have problems such as inhibiting hydration performance, reducing filtration loss performance and weak temperature resistance, which makes it difficult to effectively control hydration and filtration loss of shale during drilling.
Polyethyleneimine modified graphene oxide composite material is used as a shale inhibitor for water-based drilling fluid. By introducing hydroxyl and carboxylic functional groups into graphene oxide and forming hydrogen bonds with polyethyleneimine, the composite material is enhanced to inhibit hydration, filtration loss and temperature resistance.
This composite material significantly improves the hydration inhibition, filtration loss reduction and temperature resistance of shale in water-based drilling fluid, and can effectively control hydration and filtration loss of shale and improve the stability and efficiency of the drilling process.
Smart Images

Figure CN119552639A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of petroleum extraction, and in particular to a polyethyleneimine modified graphene oxide composite material and a preparation method and application thereof. Background Art
[0002] At present, the commonly used shale inhibitors in drilling fluids include inorganic salt shale inhibitors such as potassium chloride, cationic ammonium salt shale inhibitors such as small cations and polyamines, etc.
[0003] The preparation process of pyranose-grafted graphene (Glu-Gr) mentioned in "Graphene grafted with glucopyranose as a shale swelling inhibitor in water-based drilling mud" (Applied Clay Science) is complicated and requires a lot of raw materials. To prepare pyranose-grafted graphene, graphene oxide nanosheets are initially reacted with SOCl2 to obtain acyl chloride-functionalized graphene oxide. Subsequently, CH2OH-capped pyranose and acyl chloride-functionalized graphene oxide are condensed to form the final product Glu-Gr.
[0004] The preparation process of polyethyleneimine grafted graphene (PEI-Gr) mentioned in "Graphene grafted with polyethyleneimine for enhanced shale inhibition in the water-based drilling fluid" (Environmental Nanotechnology, Monitoring & Management) is complicated and time-consuming, requires a lot of raw materials, and uses hydrogen peroxide as a reducing substance; the solvent used to prepare the final product is tetrahydrofuran, which needs to react for 2 days under the action of a catalyst.
[0005] The above shale inhibitors have the disadvantages of large dosage, great environmental pollution, weak temperature resistance, weak filtration reduction performance and weak hydration inhibition performance. Therefore, it is necessary to develop shale inhibitors with better performance. Summary of the invention
[0006] The purpose of the present invention is to overcome the problems of the prior art in terms of weak hydration inhibition, filtration loss reduction and temperature resistance, and to provide a polyethyleneimine modified graphene oxide composite material and a preparation method and application thereof.
[0007] In order to achieve the above-mentioned object, the first aspect of the present invention provides a polyethyleneimine-modified graphene oxide composite material, wherein the composite material comprises: polyethyleneimine and graphene oxide with multi-functional groups; the total content of hydroxyl and carboxyl groups contained in the graphene oxide is 4-6wt%; and there is a hydrogen bond between the nitrogen atom of the amino group contained in the polyethyleneimine and the oxygen atom in the graphene oxide.
[0008] A second aspect of the present invention provides a method for preparing a polyethyleneimine modified graphene oxide composite material, comprising:
[0009] (1) subjecting a single layer of graphite to an oxidation reaction with an oxidant, and then subjecting the obtained product to a reduction reaction with a reducing agent to obtain graphene oxide;
[0010] (2) reacting the graphene oxide and polyethyleneimine to obtain the composite material;
[0011] Wherein, the mass ratio of the reducing agent to the single-layer graphite is 1-1.5:100.
[0012] The third aspect of the present invention provides a polyethyleneimine modified graphene oxide composite material obtained by the preparation method.
[0013] A fourth aspect of the present invention provides an application of the polyethyleneimine modified graphene oxide composite material as a shale inhibitor for water-based drilling fluids.
[0014] Through the above technical scheme, the polyethyleneimine modified graphene oxide composite material provided by the present invention has excellent hydration inhibition performance, filtration loss reduction performance and temperature resistance when used as a shale inhibitor for water-based drilling fluid. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 is the infrared spectrum of the polyethyleneimine modified graphene oxide composite material of Example 1;
[0016] Figure 2 It is the rolling recovery rate of XC, GO1 / XC, S1 / XC, S2 / XC, S3 / XC, S4 / XC, S5 / XC, S6 / XC, D1 / XC and D2 / XC. DETAILED DESCRIPTION
[0017] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0018] The first aspect of the present invention provides a polyethyleneimine-modified graphene oxide composite material, wherein the composite material comprises: polyethyleneimine and graphene oxide with multi-functional groups; the total content of hydroxyl and carboxyl groups contained in the graphene oxide is 4-6wt%; and hydrogen bonds exist between the nitrogen atoms of the amino groups contained in the polyethyleneimine and the oxygen atoms in the graphene oxide.
[0019] In the present invention, the multifunctional groups of the graphene oxide are selected from hydroxyl and / or carboxyl. The composite material contains oxygen-containing functional groups in the graphene oxide, and the oxygen atoms therein can form hydrogen bonds with the nitrogen atoms of the amino groups contained in the polyethyleneimine, so that the composite material has excellent hydration inhibition performance, fluid loss reduction performance and temperature resistance. The polyethyleneimine has a hyperbranched structure, and the branching degree of the polyethyleneimine is 30-35%, which can be commercially obtained, and the contact points with the graphene oxide are increased. There are hydrogen bonds between the amino groups contained therein and the oxygen atoms in the oxygen-containing functional groups (hydroxyl and carboxyl) in the graphene oxide. When the total content of hydroxyl and carboxyl groups contained in the graphene oxide is within the range of 4-6wt%, the polyethyleneimine-modified graphene oxide composite material can have excellent hydration inhibition performance, fluid loss reduction performance and temperature resistance.
[0020] In some specific embodiments of the present invention, the weight average molecular weight of the polyethyleneimine is 5000-15000 g / mol. When the weight average molecular weight of the polyethyleneimine is within this range, the polyethyleneimine contains more amino sites, which increases the contact points with the graphene oxide, and the obtained polyethyleneimine-modified graphene oxide composite material has excellent hydration inhibition performance, filtration loss reduction performance and temperature resistance.
[0021] In some specific embodiments of the present invention, in the composite material, the mass ratio of the polyethyleneimine to the graphene oxide is 2-10:1. When the mass ratio is less than 2:1, the composite material will have too little polyethyleneimine to provide too few amino groups that can chemically inhibit hydration. When the mass ratio is greater than 10:1, there is too much polyethyleneimine that cannot be compounded with graphene oxide in the composite material, inhibiting hydration to reach saturation. Therefore, when the mass ratio of the polyethyleneimine to the graphene oxide is 2-10:1, the polyethyleneimine-modified graphene oxide composite material has excellent hydration inhibition performance. The mass ratio of the polyethyleneimine to the graphene oxide is preferably 9-10:1, so that the polyethyleneimine-modified graphene oxide composite material has excellent hydration inhibition performance, fluid loss reduction performance and temperature resistance.
[0022] In some specific embodiments of the present invention, the composite material has a hydration inhibition performance of: the composite material with a concentration of 0.4wt% reduces the swelling height caused by hydration of bentonite by 50-55%. The composite material of the present invention has excellent hydration inhibition performance.
[0023] A second aspect of the present invention provides a method for preparing a polyethyleneimine modified graphene oxide composite material, comprising:
[0024] (1) subjecting a single layer of graphite to an oxidation reaction with an oxidant, and then subjecting the obtained product to a reduction reaction with a reducing agent to obtain graphene oxide;
[0025] (2) reacting the graphene oxide and polyethyleneimine to obtain the composite material;
[0026] Wherein, the mass ratio of the reducing agent to the single-layer graphite is 1-1.5:100.
[0027] In some specific embodiments of the present invention, in step (1), before the oxidation reaction, the graphite and concentrated sulfuric acid are firstly exfoliated to obtain a single layer of graphite, and the weight ratio of the graphite to the concentrated sulfuric acid is 1:35-38.
[0028] In some specific embodiments of the present invention, in step (1), the oxidant is selected from one or more of sodium nitrate, potassium permanganate, and nitric acid.
[0029] In some specific embodiments of the present invention, the reducing agent is selected from hydrazine hydrate.
[0030] In some specific embodiments of the present invention, relative to 100 parts by weight of the graphite, the oxidant is 200-400 parts by weight, and the reducing agent is 1-1.5 parts by weight.
[0031] In some specific embodiments of the present invention, the temperature of the oxidation reaction is 90-95° C.; the time of the oxidation reaction is 1.5-2 h.
[0032] In some specific embodiments of the present invention, the temperature of the reduction reaction is 20-30° C.; the time of the reduction reaction is 20-30 min.
[0033] In some specific embodiments of the present invention, the reaction temperature is 60-80° C., and the reaction time is 6-8 h.
[0034] In some specific embodiments of the present invention, the mass ratio of polyethyleneimine to graphene oxide is 2-10:1, preferably 9-10:1.
[0035] In some specific embodiments of the present invention, in the step (2), the graphene oxide is first dissolved in water before the reaction, and the concentration of the graphene oxide in water is 0.5-2wt%.
[0036] The third aspect of the present invention provides a polyethyleneimine modified graphene oxide composite material obtained by the preparation method.
[0037] A fourth aspect of the present invention provides an application of the polyethyleneimine modified graphene oxide composite material as a shale inhibitor for water-based drilling fluids.
[0038] The present invention will be described in detail below through examples.
[0039] The expansion height is measured using a linear expansion instrument. The test method is shown in Test Example 1.
[0040] Medium pressure filtration loss (API, mL) was measured using a filter loss meter according to the American Petroleum Institute (API) specification and Chinese SY / T5621-93 standard.
[0041] The total content of hydroxyl and carboxyl groups in graphene oxide was measured by Boehm titration.
[0042] The manufacturer of the linear expansion instrument is Qingdao Haitongda, model CPZ-2.
[0043] The manufacturer of the filtration instrument is Qingdao Bairuida, model ZNZ-S5.
[0044] The manufacturer of the high temperature roller furnace is Qingdao Haitongda, model BGRL-5.
[0045] In the following examples and comparative examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are all conventional products that can be obtained through commercial channels.
[0046] Preparation Example 1: Preparation of graphene oxide
[0047] Add 6g of graphite powder (325 mesh) to 120mL of concentrated sulfuric acid (concentration of 98.3wt%) (0℃), stir and add until fully dissolved, then add 3g of NaNO3. After NaNO3 is completely dissolved, slowly add 15g of KMnO4, stirring and adding, and keep the temperature below 20℃ in an ice bath system. Stir the mixture at 35℃ for 2h, then add 250mL of deionized water to dilute, and keep the temperature below 50℃ in an ice bath system during the dilution process. After the dilution is completed, stir the mixture for 2h, then heat it to 90℃ and react for 15min. Then pour the solution into 700mL of deionized water and cool it to room temperature. Slowly add 0.06mL of hydrazine hydrate to obtain a golden liquid. After standing overnight, the supernatant was removed, and the lower liquid was centrifuged at 8000rpm for 20min. The precipitate was washed with hydrochloric acid at a volume ratio of 1:10, and then washed three times with deionized water. The washing operation was repeated more than three times until the pH of the solution was neutral. The obtained solution was dialyzed with a dialysis bag with a molecular weight cutoff of 3500 for 2 weeks. The water was changed more than twice a day. The dialyzed solution was freeze-dried with a freeze dryer to obtain weakly reduced graphene oxide GO1;
[0048] Among them, the total content of hydroxyl and carboxyl groups in graphene oxide GO1 is 6wt%.
[0049] Preparation Example 2: Preparation of graphene oxide
[0050] Add 6g of graphite powder (325 mesh) to 120mL of concentrated sulfuric acid (concentration of 98.3wt%) (0℃), stir and add until fully dissolved, then add 3g of NaNO3. After NaNO3 is completely dissolved, slowly add 15g of KMnO4, stirring and adding, and keep the temperature below 20℃ in an ice bath system. Stir the mixture at 35℃ for 2h, then add 250mL of deionized water for dilution, and keep the temperature below 50℃ in an ice bath system during the dilution process. After the dilution is completed, stir the mixture for 2h, then heat it to 90℃ and react for 15min. Then pour the solution into 700mL of deionized water and cool it to room temperature. Slowly add 0.2mL of hydrazine hydrate to obtain a golden liquid. After standing overnight, the supernatant was removed, and the lower liquid was centrifuged at 8000rpm for 20min. The precipitate was washed with hydrochloric acid at a volume ratio of 1:10, and then washed three times with deionized water. The washing operation was repeated more than three times until the pH of the solution was neutral. The obtained solution was dialyzed with a dialysis bag with a molecular weight cutoff of 3500 for 2 weeks. The water was changed more than twice a day. The dialyzed solution was freeze-dried with a freeze dryer to obtain graphene oxide GO2;
[0051] Among them, the total content of hydroxyl and carboxyl groups in graphene oxide GO2 is 4wt%.
[0052] Comparative Preparation Example 1: Preparation of Graphene Oxide
[0053] Add 6g of graphite powder (325 mesh) to 120mL of concentrated sulfuric acid (concentration of 98.3wt%) (0℃), stir and add until fully dissolved, then add 3g of NaNO3. After NaNO3 is completely dissolved, slowly add 15g of KMnO4, stirring and adding, and keep the temperature below 20℃ in an ice bath system. Stir the mixture at 35℃ for 2h, then add 250mL of deionized water to dilute, and keep the temperature below 50℃ in an ice bath system during the dilution process. After the dilution is completed, stir the mixture for 2h, then heat it to 90℃ and react for 15min. Then pour the solution into 700mL of deionized water and cool it to room temperature. Slowly add 0.5mL of hydrazine hydrate to obtain a golden liquid. After standing overnight, the supernatant was removed, and the lower liquid was centrifuged at 8000rpm for 20min. The precipitate was washed with hydrochloric acid at a volume ratio of 1:10, and then washed three times with deionized water. The washing operation was repeated more than three times until the pH of the solution was neutral. The obtained solution was dialyzed with a dialysis bag with a molecular weight cutoff of 3500 for 2 weeks. The water was changed more than twice a day. The dialyzed solution was freeze-dried with a freeze dryer to obtain graphene oxide GO3;
[0054] Among them, the total content of hydroxyl and carboxyl groups in graphene oxide GO3 is 1wt%.
[0055] Example 1
[0056] 1 g of graphene oxide GO1 obtained in Preparation Example 1 was added to 99 mL of deionized water, and ultrasonic treatment was performed for 30 minutes to prepare a GO1 solution with a concentration of 1 wt%; 10 g of polyethyleneimine (PEI, hyperbranched structure, branching degree of 35%, molecular weight of 10000 g / mol) was added to the GO1 solution according to a mass ratio of polyethyleneimine to graphene oxide of 10:1; the solution was stirred at 80° C. for 6 hours to obtain a black opaque polyethyleneimine-modified graphene oxide composite material, which was recorded as S1.
[0057] Example 2
[0058] 1 g of graphene oxide GO2 obtained in Preparation Example 2 was added to 99 mL of deionized water, and ultrasonic treatment was performed for 30 minutes to prepare a GO2 solution with a concentration of 1 wt%; 10 g of polyethyleneimine (PEI, hyperbranched structure, branching degree of 35%, molecular weight of 10000 g / mol) was added to the GO2 solution according to a mass ratio of polyethyleneimine to graphene oxide of 10:1; the solution was stirred at 80°C for 6 hours to obtain a black opaque polyethyleneimine-modified graphene oxide composite material, recorded as S2.
[0059] Example 3
[0060] 1 g of graphene oxide GO1 obtained in Preparation Example 1 was added to 99 mL of deionized water, and ultrasonic treatment was performed for 30 minutes to prepare a GO1 solution with a concentration of 1 wt%; 10 g of polyethyleneimine (PEI, hyperbranched structure, branching degree of 35%, molecular weight of 5000 g / mol) was added to the GO1 solution according to a mass ratio of polyethyleneimine to graphene oxide of 10:1; the solution was stirred at 80°C for 6 hours to obtain a black opaque polyethyleneimine-modified graphene oxide composite material, recorded as S3.
[0061] Example 4
[0062] 1 g of graphene oxide GO1 obtained in Preparation Example 1 was added to 99 mL of deionized water, and ultrasonic treatment was performed for 30 minutes to prepare a GO1 solution with a concentration of 1 wt%; 10 g of polyethyleneimine (PEI, hyperbranched structure, branching degree of 35%, molecular weight 1800 g / mol) was added to the GO1 solution according to a mass ratio of polyethyleneimine to graphene oxide of 10:1; the solution was stirred at 80°C for 6 hours to obtain a black opaque polyethyleneimine-modified graphene oxide composite material, recorded as S4.
[0063] Example 5
[0064] 1 g of graphene oxide GO1 obtained in Preparation Example 1 was added to 99 mL of deionized water, and ultrasonic treatment was performed for 30 minutes to prepare a GO1 solution with a concentration of 1 wt%; 5 g of polyethyleneimine (PEI, hyperbranched structure, branching degree of 35%, molecular weight of 10000 g / mol) was added to the GO1 solution according to a mass ratio of polyethyleneimine to graphene oxide of 5:1; the solution was stirred at 80°C for 6 hours to obtain a black opaque polyethyleneimine-modified graphene oxide composite material, recorded as S5.
[0065] Example 6
[0066] 1 g of graphene oxide GO1 obtained in Preparation Example 1 was added to 99 mL of deionized water, and ultrasonic treatment was performed for 30 minutes to prepare a GO1 solution with a concentration of 1 wt%; 2 g of polyethyleneimine (PEI, hyperbranched structure, branching degree of 35%, molecular weight of 10000 g / mol) was added to the GO1 solution according to a mass ratio of polyethyleneimine to graphene oxide of 2:1; the solution was stirred at 80°C for 6 hours to obtain a black opaque polyethyleneimine-modified graphene oxide composite material, recorded as S6.
[0067] Comparative Example 1
[0068] 1 g of graphene oxide GO3 obtained in Comparative Preparation Example 1 was added to 99 mL of deionized water, and ultrasonic treatment was performed for 30 minutes to prepare a GO3 solution with a concentration of 1 wt%; 10 g of polyethyleneimine (PEI, hyperbranched structure, branching degree of 35%, molecular weight 10000 g / mol) was added to the GO3 solution according to a mass ratio of polyethyleneimine to graphene oxide of 10:1; the solution was stirred at 80°C for 6 hours to obtain a black opaque polyethyleneimine-modified graphene oxide composite material, recorded as D1.
[0069] Comparative Example 2
[0070] 1 g of commercially available graphene oxide GO4 was added to 99 mL of deionized water and ultrasonically treated for 30 minutes to prepare a GO4 solution with a concentration of 1 wt%; 10 g of polyethyleneimine (PEI, hyperbranched structure, branching degree of 35%, molecular weight of 10000 g / mol) was added to the GO4 solution according to the mass ratio of polyethyleneimine to graphene oxide of 10:1; the solution was stirred at 80°C for 6 hours to obtain a black opaque polyethyleneimine-modified graphene oxide composite material, recorded as D2.
[0071] Structural characterization:
[0072] The infrared spectrum test of polyethyleneimine modified graphene oxide composite material S1 was carried out, and the results were as follows Figure 1 The mass of hydrogen atoms after hydrogen bond formation decreases, causing the peak to shift to a lower wave number. In the spectrum of GO1 / bentonite, the stretching vibration peak of hydroxyl OH can be observed at 3468 cm -1 OH was observed at 3414 cm in the spectrum of S1 / bentonite. -1 The red shift of the peak indicates that there is a hydrogen bond between polyethyleneimine and graphene oxide.
[0073] Test Example 1: Evaluation of the Hydration Inhibition Performance of Composite Materials
[0074] The laboratory used a linear expansion instrument to measure the swelling height of bentonite in deionized water and different inhibitor solutions over time. 5g of bentonite was poured into a pressure tank and a hydraulic press was used to apply a pressure of 5MPa for 10 minutes to make a soil block. After the linear expansion instrument value was reset to zero, the soil block was placed, and then the test was started and water and inhibitor solutions of different concentrations were injected to measure the swelling height of bentonite over time, where the concentration of GO1, S1, S2, S3, S4, S5, S6, D1, and D2 solutions was 0.4wt%, and the concentration of KCl solution was 4wt%. The results are shown in Table 1.
[0075] Table 1
[0076]
[0077] As shown in Table 1, in the study of linear expansion test, bentonite was hydrated in deionized water, 0.4wt% GO1, S1, S2, S3, S4, S5, S6, D1 and D2 solutions, and 4wt% KCl solution for 16 hours, causing swelling heights of 5.82mm, 4.24mm, 2.74mm, 2.82mm, 2.91mm, 3.09mm, 3.01mm, 3.11mm, 2.92mm, 2.88mm and 2.96mm, respectively. The data showed that compared with deionized water, the swelling height caused by 0.4wt% concentration of S1 was reduced by 3.08mm, a decrease of 52.9%, and its hydration inhibition effect was excellent. At the same time, it can be observed that the inhibition performance of S1 is better than other graphene composites, graphene oxide GO1 and KCl, and the concentration of S1 is 1 / 10 of KCl. Compared with other graphene composite materials of the same concentration, the swelling height caused by S1 is reduced by 0.08-0.35mm. In addition to the pore blocking effect provided by graphene oxide as a nanomaterial, there are a large number of amino groups brought by polyethyleneimine on the surface of S1. The amino groups are adsorbed on the surface and side of the clay through hydrogen bonds and electrostatic adsorption, preventing water intrusion. S1 can significantly improve the ability of GO to inhibit hydration. When the molecular weight of polyethyleneimine is 10000g / mol, since the number of hydroxyl groups of graphene oxide GO2, GO3 and GO4 used in Example 2, Comparative Example 1 and Comparative Example 2 is less than GO1, the obtained S2, D1 and D2 have a lower combination rate of graphene oxide and polyethyleneimine, and less amino groups that can chemically inhibit hydration. When the graphene oxide used is the graphene oxide GO1 obtained in Preparation Example 1, since the molecular weight of the polyethyleneimine used in Example 3 and Example 4 is different, the polyethyleneimine provided on the obtained S3 and S4 has fewer amino groups, so the chemical hydration inhibition ability is lower. When the mass ratio is different, the polyethyleneimine content in Example 5 and Example 6 is lower, and fewer amino groups are provided, so the chemical hydration inhibition ability of S5 and S6 is lower.
[0078] Test Example 2: Evaluation of the anti-filtration performance of composite materials
[0079] Preparation of xanthan gum solution: Pour 0.9g xanthan gum (XC) into 300mL deionized water and stir until XC is dissolved to obtain 0.3wt% XC solution, then pour 0.6g of different nanomaterials into the XC solution and stir to prepare 0.2wt% GO1, S1, nano-silicon oxide, amino nano-silicon oxide, nano-zinc oxide, and graphite powder solutions. A medium-pressure filtration device was used to measure the changes in the filtration loss of GO1 and S1 solutions within 30 minutes and the filtration loss of the remaining nanomaterials after 30 minutes of testing. The filter paper was replaced with a polytrifluoroethylene membrane (220nm) to better simulate the pore size of shale. The measured filtration loss is shown in Table 2-3.
[0080] Table 2
[0081]
[0082] Table 3
[0083] Inhibitors GO1 S1 Nano silicon oxide Amino Nano Silica Nano zinc oxide Graphite powder Filtration loss / mm 8.8 8.2 34.5 36 30.5 32
[0084] The plugging ability is evaluated by the filtration volume. The smaller the filtration volume, the better the plugging ability. As shown in Table 2, the filtration loss growth curves of S1 solution and GO1 solution are similar, and the filtration loss of S1 solution is less than that of GO1 solution. The plugging process of GO1 and S1 is that graphene oxide and graphene composite materials are adsorbed on the surface of filter paper or membrane to form a smooth film, which prevents water from passing through the filter paper or membrane. Compared with GO1 and S1 solutions, no film is formed in other nanomaterial solutions, and a large number of aggregated microparticles are observed. These microparticles cannot form a tight filter cake due to aggregation. The plugging ability of GO1 and S1 is much better than that of other inorganic nanomaterials. As shown in Table 3, under certain specific conditions, compared with the rest of the nanomaterials, the drilling fluid with S1 added has the lowest filtration loss, among which the filtration loss of GO1 and S1 is 8.8mL and 8.2mL, respectively, which is close to the filtration loss of commonly used filtration reducers. The filtration volumes of other nanomaterials were 34.5 mL, 36 mL, 30.5 mL, and 32 mL, indicating that part of the water passed through the filter paper.
[0085] Test Example 3: Evaluation of high temperature resistance of composite materials
[0086] The shale was crushed and sieved between 6-10 mesh. 20g of shale debris was poured into an aging tank containing 300mL of XC, GO1 / XC, S1 / XC, S2 / XC, S3 / XC, S4 / XC, S5 / XC, S6 / XC, D1 / XC and D2 / XC solutions. The concentration of XC is 0.3wt%, and the concentration of GO1, S1, S2, S3, S4, S5, S6, D1D2 is 0.2wt%. The aging tank was placed in a high-temperature roller furnace and hot-rolled at 120℃ for 16h, dried at 105℃ for 48h, and weighed after sieving through 40 mesh. The mass of shale before hot rolling is recorded as W1, and the mass of shale after hot rolling is recorded as W2. The calculation formula for rolling recovery is as follows: Recovery rate = W2 / W1. The measured rolling recovery rate is as follows Figure 2 shown.
[0087] like Figure 2As shown, the rolling recovery rates of XC, GO1 / XC, S1 / XC, S2 / XC, S3 / XC, S4 / XC, S5 / XC, S6 / XC, D1 / XC and D2 / XC are 36.24%, 37.27%, 74.56%, 72.91%, 70.21%, 66.15%, 68.55%, 65.78%, 70.92% and 69.02%, respectively. This further indicates that the inhibition ability of graphene composites is still better than that of graphene oxide under high temperature conditions, and the inhibition performance of S1 is better than that of other composites.
[0088] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A polyethyleneimine modified graphene oxide composite material, characterized in that: The composite material comprises: polyethyleneimine and graphene oxide with multiple functional groups; the total content of hydroxyl groups and carboxyl groups contained in the graphene oxide is 4-6wt%; and hydrogen bonds exist between nitrogen atoms of the amino groups contained in the polyethyleneimine and oxygen atoms in the graphene oxide.
2. The composite material according to claim 1, characterized in that The weight average molecular weight of the polyethyleneimine is 5000-15000 g / mol; Preferably, the branching degree of the polyethyleneimine is 30-35%.
3. The composite material according to claim 1 or 2, characterized in that: In the composite material, the mass ratio of the polyethyleneimine to graphene oxide is 2-10:1, preferably 9-10:
1.
4. The composite material according to any one of claims 1 to 3, characterized in that The composite material with a concentration of 0.4wt% reduces the swelling height caused by hydration of bentonite by 50-55%.
5. A method for preparing a polyethyleneimine modified graphene oxide composite material, characterized in that: include: (1) subjecting a single layer of graphite to an oxidation reaction with an oxidant, and then subjecting the obtained product to a reduction reaction with a reducing agent to obtain graphene oxide; (2) reacting the graphene oxide and polyethyleneimine to obtain the composite material; Wherein, the mass ratio of the reducing agent to the single-layer graphite is 1-1.5:
100.
6. The preparation method according to claim 5, characterized in that: in, In step (1), before the oxidation reaction, the graphite is firstly exfoliated with concentrated sulfuric acid to obtain a single layer of graphite; Preferably, the weight ratio of graphite to concentrated sulfuric acid is 1:35-38; Preferably, the oxidant is selected from one or more of sodium nitrate, potassium permanganate, and nitric acid; Preferably, the reducing agent is selected from hydrazine hydrate; Preferably, relative to 100 parts by weight of the graphite, the oxidant is 200-400 parts by weight, and the reducing agent is 1-1.5 parts by weight; Preferably, the temperature of the oxidation reaction is 90-95°C; the time of the oxidation reaction is 1.5-2h; Preferably, the temperature of the reduction reaction is 20-30°C; the time of the reduction reaction is 20-30min.
7. The preparation method according to claim 5 or 6, characterized in that: In step (2), the reaction temperature is 60-80°C, and the reaction time is 6-8h.
8. The preparation method according to any one of claims 5 to 7, characterized in that: The mass ratio of polyethyleneimine to graphene oxide is 2-10:1, preferably 9-10:1; Preferably, in step (2), the graphene oxide is dissolved in water before the reaction, and the concentration of the graphene oxide in water is 0.5-2 wt %.
9. A polyethyleneimine-modified graphene oxide composite material obtained by the preparation method according to any one of claims 5 to 8.
10. Use of the polyethyleneimine modified graphene oxide composite material according to any one of claims 1 to 4 and 9 as a shale inhibitor for water-based drilling fluid.
Citation Information
Patent Citations
Preparation method of water-dispersible conducting graphene
CN106744834A
Plugging agent composition, water-based drilling fluid and application of water-based drilling fluid
CN107163920A
Strong-suppression strong-sealing water-based drilling fluid suitable for shale formations, and preparation method thereof
CN109837072A
Polyethylenimine modified graphene oxide and epoxy nano composite material thereof
CN109929141A
Graphene aerogel and preparation method thereof
CN115849350A